Ovarian clear cell carcinoma with plasma cell‐rich inflammatory stroma: Cytological Findings of a Case. Issue 2 (8th October 2016) - Shintaku, Masayuki; Dohi, Makoto; Yamamoto, Yoshihiro; Nagai, Aya; Higuchi, Toshihiro
Abstract : We report a case of clear cell carcinoma (CCC) of the ovary with plasma cell‐rich inflammatory stroma, a recently proposed subtype of CCC, and present the cytological findings. The patient was a 48‐year‐old woman, who was incidentally found to have a right ovarian tumor during the preoperative work‐up for an early‐stage adenocarcinoma of the uterine cervix. Cytological examination of an imprint smear of the ovarian tumor and peritoneal washing revealed solid cell clusters of irregular, often dendritic shapes, which were intermingled with many inflammatory cells. "Raspberry bodies" were not found. Histopathological examination of the extirpated ovarian tumor showed the features of CCC with plasma cell‐rich inflammatory stroma. This subtype of ovarian CCC poses cytological and histological diagnostic problems, and its differentiation from dysgerminoma is often difficult, because it mostly lacks the hyaline or mucoid stroma. Irregularly shaped clusters of large polyhedral cells, coarsely clumped nuclear chromatin, and plasma cell‐rich inflammatory infiltrates suggest CCC, but the cytological differences between dysgerminoma and CCC are often subtle, and immunohistochemical examinations for cytokeratin 7 or epithelial membrane antigen may be necessary. Diagn. Cytopathol. 2017;45:128–132. © 2016 Wiley Periodicals, Inc.